Analisis Kemampuan Multirepresentasi Peserta Didik Dalam Menyelesaikan Masalah Pada Materi Usaha Dan Energi - Reza Alifiyah Safitri; Abu Zainuddin (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to describe the multi-representation instrument's feasibility and analyze students' multi-representation ability in solving problems regarding work and energy materials. This research uses a mixed methods approach with sequential explanatory design. The analysis results show that seven items are feasible to measure students' multi-representation abilities. Students' level of multi-representation ability in solving problems on work and energy material in the category needs some improvement 20%, inadequate 69%, and missing 11%. Students in the needs some improvement category were interested in the format of the questions used in the test. However, students still have difficulty representing the problem. They made some efforts to understand the problem, answered according to the steps, and had a strategy to answer the question correctly. Students in the inadequate category had difficulty representing the problem but still had a strategy to answer it. Meanwhile, students in the missing category struggled to represent the problem because they did not have steps and strategies to answer.